The Role of the Audit Board of Indonesia (BPK) in Enhancing Transparency of Regional Financial Management: Evidence from Medan City Government in 2024 - Dian Eka Zahra; Aliska Putri Simatupang; Vania Ailsa Nabilah; Putri Kemala Dewi Lubis; Nela Permata Sari Lubis (Brilliant International Journal Of Management And Tourism, 2026)
Research This aim For analyze role BPK 's strategic push transparency And accountability finance Medan City Government through method qualitative descriptive based studies Literature Review Report Number 131.B/S/XVIII.MDN/05/2024. The results of the study indicate that the Audit Board of Indonesia (BPK) acts as an instrument of radical transparency by uncovering information asymmetry in public funds. Despite achieving an unqualified opinion (WTP), an overpayment of Rp4.44 billion in official travel expenses and a shortfall in regional taxes of Rp5.01 billion were found, indicating weaknesses in internal control. The effectiveness of the BPK is strengthened by binding recommendations in accordance with Law Number 15 of 2004 with a 60-day follow-up deadline. The study concludes that the BPK's independent oversight is a key catalyst for improving regional financial structures for the public interest.